CFTR High Expresser Cells in cystic fibrosis and intestinal diseases - Diego Carlos dos Reis; Parinaz Dastoor; Anderson Kenedy Santos; Kaelyn Sumigray; Nadia A. Ameen (Heliyon, 2023)
Cystic Fibrosis Transmembrane Conductance Regulator (CFTR), the Cl−/HCO3− channel implicated in Cystic Fibrosis, is critical to the pathophysiology of many gastrointestinal diseases. Defects in CFTR lead to intestinal dysfunction, malabsorption, obstruction, infection, inflammation, and cancer that increases morbidity and reduces quality of life. This review will focus on CFTR in the intestine and the implications of the subpopulation of CFTR High Expresser Cells (CHEs) in Cystic Fibrosis (CF), intestinal physiology and pathophysiology of intestinal diseases.